Attitude and Perception of Nasarawa State Residents towards COVID-19 Television Awareness Campaign - Musa Mathias; Gana Hope (Kwaghe International Journal of Arts, Humanities and Religious Studies, 2026)
Television emerged as a key platform for COVID-19 awareness campaigns due to its wide reach, credibility, and capacity to convey complex health information through audio-visual messages. This study examined the attitudes and perceptions of residents of Nasarawa State toward television-based COVID-19 awareness campaigns, with specific attention to vaccination messaging. Anchored in agenda-setting theory, the study adopted a descriptive survey design to investigate how television reportage on COVID-19 vaccination influenced public perceptions and health-related behaviors. The findings indicate that residents generally held positive and favorable perceptions of television coverage on COVID-19, particularly vaccination awareness campaigns broadcast by local and satellite stations. Television messages were reported to have positively shaped attitudes toward adherence to COVID-19 safety protocols and uptake of the COVID-19 vaccine, contributing to Nasarawa State’s strong performance in national vaccination rankings. The study concludes that television awareness campaigns played a significant role in promoting compliance with public health measures during the pandemic and underscores the need to sustain and extend such media efforts to other priority health issues. It recommends that policymakers develop enabling policies that empower media organizations, especially television stations—to conduct proactive, regular health communication campaigns, thereby strengthening preparedness and response during future health emergencies.